PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUASAN KONSUMEN KFC (Studi Kasus KFC Jln. Ratulangi Palopo) - Iren Marsela; Putri Reski Utama; Adolpina Patinggi; Nasruddin; Nurjannah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
In the current era of globalization, it is quite challenging to predict economic growth and development. Changes in the global economy, social structure, and cultural landscape are to blame. It goes without saying that this will also impact how the global economy is structured. Changes in people's consumption habits have given birth to concepts that are beneficial to the food service industry, one of which is fast food. Many investors in the fast food sector are taking advantage of this economic opportunity. Fast food is ready-to-eat food that can be eaten immediately, such as fried chicken, hamburgers and pizza. Because it is easy to find ready-to-eat food on the market, a variety of foods can be offered according to taste and income. Plus, it takes less time and effort to prepare, making it ideal for people who are always on the go. In today's economy, some customers choose KFC over other fast food restaurants. Therefore, this research set limits on consumers of KFC fast food restaurants in the Palopo area, South Sulawesi. Because it is located close to the market and hypermarket, in terms of competition there are other fast food outlets in this place, such as Ok Bento and McDonald's. So with the many fast food outlets available, KFC always satisfies consumers.